Shifting Harbor Seal ( Phoca vitulina ) Diet May Reflect Ecosystem Changes in Skagerrak - Foteini Kappa; Tero Härkönen; Carla Freitas; Daire Carroll; Karin C. Harding (Marine Mammal Science, 2026)
Harbor seals, as generalist predators, can adjust their diet in response to shifts in prey availability; thus, their diet composition has the potential to act as a biodiversity indicator. This study examined the diet of harbor seals in the Skagerrak by analyzing otoliths from scat samples collected in 2020 and compared species composition to historical datasets from 1977/78 and 1989. The diet in 2020 encompassed 28 fish species. Sandeel and Norway pout were the most common prey, comprising 39.6% and 21.8% of otoliths, respectively. The group haddock/pollack/saithe and ballan wrasse had the highest relative biomass contributions: 18.7% and 13.5%, respectively. A comparison with historical data revealed a shift in diet, with a notable decline in cod and herring consumption and an increase in sandeel and haddock/pollack/saithe. The findings suggest a dietary adaptation of harbor seals to available prey species. The reduced intake of energy‐rich prey like herring raises concerns about whether current diet composition can meet the seals' energetic needs. The observed dietary changes may reflect changes in prey availability due to environmental and anthropogenic factors, emphasizing the importance of continued studies to assess the implications for harbor seal populations in the region.

Harbor Seals ( Phoca vitulina ) Sighted 34 Years After Their Inclusion in a Capture‐Mark‐Recapture Study - Daire Carroll; Jessica Harvey‐Carroll; Tero Härkönen; Karin C. Harding (Marine Mammal Science, 2026)

Characterization of the internal working-life exposome using minimally and non-invasive sampling methods - a narrative review - Eline Verscheure; Rob Stierum; Vivi Schlünssen; Anne Mette Lund Würtz; Dorian Vanneste; Manolis Kogevinas; Barbara N. Harding; Karin Broberg; Shan Zienolddiny-Narui; Johanna Samulin Erdem; Mrinal K. Das; Konstantinos C. Makris; et al. (Environmental Research, 2023)

Maternal Transfer and Long-Term Population Effects of PCBs in Baltic Grey Seals Using a New Toxicokinetic–Toxicodynamic Population Model - Karl Mauritsson; Jean-Pierre Desforges; Karin C. Harding (Archives of Environmental Contamination and Toxicology, 2022)
Empirical evidence has shown that historical exposure of polychlorinated biphenyls (PCBs) to Baltic grey seals not only severely affected individual fitness, but also population growth rates and most likely caused the retarded recovery rate of the depleted population for decades. We constructed a new model which we term a toxicokinetic–toxicodynamic (TKTD) population model to quantify these effects. The toxicokinetic sub-model describes in detail the bioaccumulation, elimination and vertical transfer from mother to offspring of PCBs and is linked to a toxicodynamic model for estimation of PCB-related damage, hazard and stress impacts on fertility and survival rates. Both sub-models were linked to a Leslie matrix population model to calculate changes in population growth rate and age structure, given different rates of PCB exposure. Toxicodynamic model parameters related to reproductive organ lesions were calibrated using published historical data on observed pregnancy rates in Baltic grey seal females. Compared to empirical data, the TKTD population model described well the age-specific bioaccumulation pattern of PCBs in Baltic grey seals, and thus, the toxicokinetic parameters, deduced from the literature, are believed to be reliable. The model also captured well the general effects of PCBs on historical population growth rates. The model showed that reduced fertility due to increased PCB exposure causes decreased vertical transfer from mother to offspring and in turn increased biomagnification in non-breeding females. The developed TKTD model can be used to perform population viability analyses of Baltic grey seals with multiple stressors, also including by-catches and different hunting regimes. The model can also be extended to other marine mammals and other contaminants by adjustments of model parameters and thus provides a test bed in silico for new substances.

Bioaccumulation of PCBs, OCPs and PBDEs in Marine Mammals From West Antarctica - Mohammed Khairy; Emily Brault; Rebecca Dickhut; Karin C. Harding; Tero Harkonen; Olle Karlsson; Kristine Lehnert; Jonas Teilmann; Rainer Lohmann (Frontiers in Marine Science, 2021)
Graphical Abstract POPs in Antarctic Mammals.

The effect of prey quality and ice conditions on the nutritional status of Baltic gray seals of different age groups - Kaarina Kauhala; Britt-Marie Bäcklin; Jari Raitaniemi; Karin C. Harding (Mammal Research, 2017)

Limited use of sea ice by the Ross seal (Ommatophoca rossii), in Amundsen Sea, Antarctica, using telemetry and remote sensing data - Anna Arcalís-Planas; Signe Sveegaard; Olle Karlsson; Karin C. Harding; Anna Wåhlin; Tero Harkonen; Jonas Teilmann (Polar Biology, 2015)

Capital and income breeding: the role of food supply - Philip A. Stephens; Alasdair I. Houston; Karin C. Harding; Ian L. Boyd; John M. McNamara (Ecology, 2014)
An aspect of life history that has seen increasing attention in recent years is that of strategies for financing the costs of offspring production. These strategies are often described by a continuum ranging from capital breeding, in which costs are met purely from endogenous reserves, to income breeding, in which costs are met purely from concurrent intake. A variety of factors that might drive strategies toward a given point on the capital–income continuum has been reviewed, and assessed using analytical models. However, aspects of food supply, including seasonality and unpredictability, have often been cited as important drivers of capital and income breeding, but are difficult to assess using analytical models. Consequently, we used dynamic programming to assess the role of the food supply in shaping offspring provisioning strategies. Our model is parameterized for a pinniped (one taxon remarkable for the range of offspring‐provisioning strategies that it illustrates). We show that increased food availability, increased seasonality, and, to a lesser extent, increased unpredictability can all favor the emergence of capital breeding. In terms of the conversion of energy into offspring growth, the shorter periods of care associated with capital breeding are considerably more energetically efficient than income breeding, because shorter periods of care are associated with a higher ratio of energy put into offspring growth to energy spent on parent and offspring maintenance metabolism. Moreover, no clear costs are currently associated with capital accumulation in pinnipeds. This contrasts with general assumptions about endotherms, which suggest that income breeding will usually be preferred. Our model emphasizes the role of seasonally high abundances of food in enabling mothers to pursue an energetically efficient capital‐breeding strategy. We discuss the importance of offspring development for dictating strategies for financing offspring production.

Linking Climate Trends to Population Dynamics in the Baltic Ringed Seal: Impacts of Historical and Future Winter Temperatures - Lisa Sundqvist; Tero Harkonen; Carl Johan Svensson; Karin C. Harding (Ambio, 2012)

Detecting Density Dependence in Recovering Seal Populations - Carl Johan Svensson; Anders Eriksson; Tero Harkonen; Karin C. Harding (Ambio, 2011)

COLONIZATION HISTORY OF THE BALTIC HARBOR SEALS: INTEGRATING ARCHAEOLOGICAL, BEHAVIORAL, AND GENETIC DATA - Tero Harkonen; Karin C. Harding; Simon J. Goodman; Kerstin Johannesson (Marine Mammal Science, 2005)

Measurement error and estimates of population extinction risk - John M. McNamara; Karin C. Harding (Ecology Letters, 2004)
It is common to estimate the extinction probability for a vulnerable population using methods that are based on the mean and variance of the long‐term population growth rate. The numerical values of these two parameters are estimated from time series of population censuses. However, the proportion of a population that is registered at each census is typically not constant but will vary among years because of stochastic factors such as weather conditions at the time of sampling. Here, we analyse how such sampling errors influence estimates of extinction risk and find sampling errors to produce two opposite effects. Measurement errors lead to an exaggerated overall variance, but also introduce negative autocorrelations in the time series (which means that estimates of annual growth rates tend to alternate in size). If time series data are treated properly these two effects exactly counter balance. We advocate routinely incorporating a measure of among year correlations in estimating population extinction risk.

Estimating quasi‐extinction risk of European harbour seals: reply to Lonergan & Harwood (2003) - Karin C. Harding; Tero Härkönen; Jesús Pineda (Ecology Letters, 2003)

The 2002 European seal plague: epidemiology and population consequences - Karin C. Harding; Tero Härkönen; Hal Caswell (Ecology Letters, 2002)
We present the first epidemiological data on the 2002 outbreak of phocine distemper virus (PDV) in European harbour seals ( Phoca vitulina ). The epizootic curve to date supports a mortality rate and probability of infection identical to that of the 1988 outbreak, which killed 58% of the population. Thus immunity is playing no significant role in the dynamics of the current outbreak. Because the timing of the outbreak is important in determining local mortality rates, we predict higher mortality rates on the European continent than in Great Britain or Ireland. A stochastic model is used to quantify how recurrent epizootics affect the long‐term growth, fluctuation, and persistence of the population. Recurrent PDV epizootics with the observed frequency and severity would reduce the long‐term stochastic growth rate of the harbour seal population by half, and significantly increase the risk of quasi‐extinction.